A framework for implementing lean in the Turkish constructionindustry - Uğurlu, Didem; Harris, Nicky; Cakir, Sevilay Demirkesen (My University, 2021)
Lean has been widely adopted in the construction industry since the last decade. However, the benefits ofpracticing Lean have not yet been well understood by construction practitioners. The low productivity andefficiency rates in construction require the implementation of innovative tools and techniques such as Leanconstruction (LC). However, it is challenging for the construction industry to adopt such new technologiesand innovative methodologies. To overcome this challenge, this paper presents a Lean implementationframework for the construction practitioners operating in Turkey. In this respect, questionnaire-basedresearch is conducted with professionals in the Turkish Construction Industry to identify the need,assessment, and implementation scheme for Lean. The framework indicates the importance of planning andmanagement in the implementation process of LC. Moreover, it provides a roadmap for the organizations toimplement LC successfully. The framework encourages organizations to analyze and identify their currentstate and create their value stream mapping along with developing a new policy and strategy for the leanculture. The results of this study are expected to guide construction practitioners with the implementation ofLC and practice the components of the framework developed in the context of this study.
Keywords: İnşaat Mühendisliği